Antecedentes contextuais dos comportamentos de cidadania organizacional: uma análise à luz da identificação organizacional - Rebolho, Ana Júlia Moreira (2017)
Organizational Citizenship Behavior (OCB) has been viewed from the perspective of organizations as an essential behavior for a better performance and effectiveness of organizations. This behavior denotes individuals' spontaneity in the execution and involvement of tasks beyond those prescribed for the execution of their formal role (ORGAN, 1988). Therefore, this study was developed with the purpose of analyzing the influence of Organizational Identification on Organizational Citizenship Behaviors from the perspective of workers in an industry. A quantitative descriptive study was carried out through Survey in an industry located in the city of Panambi, in the state of Rio Grande do Sul. Initially, a questionnaire was applied, which obtained 356 respondents, from the model of Dekas et al. (2013) and validated in the Brazilian context by Andrade (2017) to verify the Organizational Citizenship Behaviors and the model of Oliveira et al. (2008) to verify the degree of Organizational Identification of workers with the organization. The data obtained were analyzed with the support of SPSS software. Among the main results are the influence of the Organizational Identification (OI) on the Organizational Citizenship Behavior, which demonstrated that OI exert ascendance on the OCB for Knowledge Workers of an industry. It should be noted that all constructs had a positive influence on the OCB. The dimension belonging to OI that had the most impact on the OCB was Identification by Imitation. These findings allow new perspectives on the themes related to this study.